The Kaiser's lost Kreuzer : a history of U-156 and Germany's long-range submarine campaign against North America, 1918 - Hodos, Paul N., 1980- (McFarland & Company, Inc., Publishers, 2017)
"In the final year of World War I, Germany made its first attempt to wage submarine warfare against faraway shores. Large, long-range U-boats torpedoed Allied shipping off the coasts of the U.S., Canada and West Africa in a desperate campaign to sidestep lethal U-boat defenses in European waters"--